Healthcare Cost Coverage and Hypertension and Diabetes Care Step Movement: A Five‐Year Follow‐Up Study in a Malaysian Semi‐Rural Community - Adeola Folayan; Quek Kia Fatt; Mark Wing Loong Cheong; Tin Tin Su (Health Science Reports)
ABSTRACT Background and Aims This study aims to understand how healthcare cost coverage (HCC) status affects hypertension and diabetes care across the three major care steps: awareness, treatment initiation and control. Methods The probability of progressing the care steps was determined with logistic regression. The backward movements of two care steps (treatment and control) were investigated using McNemar's tests and presented with a Sankey diagram. All results were disintegrated by HCC status. Result There was no evidence that having HCC contributed to any care step progression. However, there was no significant backward movement for diabetes treatment and blood pressure control for those with HCC, while those without HCC had a significant backward movement for diabetes treatment (54.3% [152/280], p < 0.001) and blood pressure control (31.6% [43/136], p = 0.04). Conclusion Our results suggest that HCC supported a reduction in backward movement for some care steps but did not contribute to care step progression. HCC policies should aim to progress enrolees from awareness to initiating treatment and achieving control to attaining long‐term hypertension and diabetes control in low‐ and middle‐income countries.